Pragmatic Issues in Arabic Heritage: Speech Acts – A Case Study - ghilous, salah; Zakour, Nazihah (El Omda in Linguistics and Discourse Analysis, 2018)
The pragmatic are not a now subject, we do not know the limits of study or method or subject of study yet. because the pragmatic’s subject progressed thanks to the efforts oxford school’s analysis and the works presented by each of( Austin, Searle ,Goff man, and each others) than contributed in progressed of pragmatic’s study, it is studied language in different contexts, she discussed and analyzed each issues lake: speech acts, conversational implicateure, deictics, and presupposition. With indicating the pragmatic’s subject, the Arabs researchers returned to heritage books for research about the achievements of old Arab researchers in this subject (pragmatic) The research discuss speech acts into grammarian’s research and application at Al- jihad’s letter. The question of this research how did they know the speech acts theory? Do the ancient grammarians as presented by the modernists today present it? And pragmatists